Deep Distance : die Entfernung der Fotografie. - Laederach, Jürg; Schürmann, Wilhelm; Zürcher, Isabel; Kunsthalle Basel (Basel : Schwabe & Co. AG, Verlag, 2000)
20th Century Fox ; ARD/WDR/NDR ; Arden, Roy ; Arnold, Eve ; Baldessari, John ; Batters, Elmer ; Bulloch, Angela ; Chalmers, Catherine ; Chaos Computer Club ; Cousteau Society ; Crewdson, Gregory ; Danke, Tobias & Raphael ; Demand, Thomas ; Deutsch, David ; Grauer, Phil ; Donen, Stanley ; Funke, Jaromir ; Gaines, Charles ; Garfield, Peter ; Greer, Fergus ; Gross, Garry ; Hay, Young ; Henle, Jan ; Herbold, Wolfgang ; Herzog, Petra ; Hinz, Volker ; Humble, John ; Jansen, Ulrich ; Jenkins, Lee ; Johnson, Larry ; Kelley, Mike ; Kilpatrick, Mell ; King, David ; Kippenberger, Martin ; Lattu, Brandon ; Lempert, Jochen ; Leonard, Zoe ; Light, Michael ; Kelly Mason, T. ; Moffatt, Tracey ; Nakagawa, Yukio ; Nyby, Christian ; Parsons, Laurie ; Piller, Peter ; Prince, Richard ; Rosefeldt, Julian ; Steinle, Piero ; Sammallahti, Pentti ; Schulthess, Armand ; Shibata, Toshio ; Signer, Roman ; Strothjohann, Ulrich ; Struth, Thomas ; Theis, Cony ; Tillmans, Wolfgang ; Vogt, Carola ; Boerboom, Peter ; Wiesehöfer, Michael ; Williams, Christopher ; Wohnseifer, Johannes ; Wolfensberger, Andrea ; Young, Terence
biog. auteurs [1 p.]
Duits
Engels
Deep Distance : die Entfernung der Fotografie, Kunsthalle Basel, 13. Mai bis 13. August 2000
boek